Triple Conjoined Nerve Root—An Unreported Anatomical Variant and Its Surgical Implications - Gassie, Kelly; Ravindran, Krishnan; Rahmathulla, Gazanfar; Deen, H. Gordon, Jr (Indian Journal of Neurosurgery, 2020)
Conjoined nerve roots are an infrequent and uncommon finding, rarely noted preoperatively. The conjoined root anomaly has potential for significant neurological injury during surgery. Preoperative recognition may avert disastrous nerve root injury but requires a high degree of clinical suspicion. We present the case of a 44-year-old patient with left L5/S1 radiculopathy caused by a herniated disc. During surgery we identified a triple conjoined nerve root anatomy. This anatomical variant, to our knowledge, has not been reported in literature. We describe the anatomical findings and surgical implications.
Keywords: conjoined nerve root; radiculopathy; anatomical variant; implications